Rodent Seed Dispersal Syndromes Follow a Downslope Trajectory, Counteracting the Climate Change‐Mediated Tree Line Elevational Shift Upwards - Ning Han; Jing Wang; Tuo Feng; Jidong Zhao; Jianghong Zhang; Xiang Hou; Gang Chang (Ecology and Evolution)
ABSTRACT Forest rodents are important mediators of plant seed dispersal and their seed caching tactics are influenced by a variety of environmental factors; however, the role of terrain slope remains uninvestigated. We examined how the dispersal of Castanea mollissima seeds by an assemblage of scatter‐hoarding rodents in the Qinling Mountains, China, was affected by slope direction and gradient in relation to seed fate. In this study, the topographic factor, which has been frequently overlooked in previous ecological studies, was investigated. It was revealed that the sloping terrain could affect the dispersal behavior of rodents toward plant seeds and ultimately influence the direction of plant dispersal. This finding brings new insights to ecological research. Overall, rodents were 1.55 more likely to transport seed downhill than uphill, and downhill mean translocation distance was 1.41 times greater than uphill, suggesting an overarching tendency for energy conservation. When comparing steep (> 35°) with shallow (< 35°) slopes, this gradient effect was strongest on gentle slopes, with other factors likely exerting a greater influence on steeper terrain. We discuss these findings both from the perspective of rodent optimal foraging in ‘landscapes of fear’ and heterogeneous ‘energy landscapes’, as well as in the context of the counteractive pressure for trees to achieve an uphill elevational shift in response to global warming.